Rockheads - Harriet Ziefert (China Walter Lorraine Books, 2004)
This zany counting book introduces a number of concepts from counting and basic addition to different words for quantities (a trio is made of three) to the number of participants required for certain activities (eleven are needed for a soccer team). Increasing numbers of rock-headed characters enjoy a variety of activities, each specific to the number on the page. Four rockheads play in a quartet, while five make a basketball team. Young readers are sure to enjoy keeping count and keeping up with these rockstars!
Keywords: Read Aloud -- Read Aloud